2012
DOI: 10.1177/1479164111434318
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-IV is a potential molecular biomarker in diabetic kidney disease

Abstract: The present study was designed to identify the changes in microvesicle-dipeptidyl peptidase-IV (DPP IV) levels in human urine and serum, and to determine whether there were correlations with the severity of diabetic kidney disease (DKD). A total of 127 patients with type 2 diabetes mellitus (T2DM) were divided into three groups according to the urinary albumin/ creatinine ratio (UACR): microalbuminuria group (n = 50); macroalbuminuria group (n = 34) and normoalbuminuria group (n = 43), and 34 age-and sex-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 29 publications
(39 reference statements)
4
113
0
1
Order By: Relevance
“…Serum DPP4 activity is also higher in T2DM individuals with IR compared to those without [16]. DPP4 is highly expressed on kidney cell surface and data are available to suggest that DPP4 levels may associated with of renal function [17]. Moreover, insulin sensitivity, assessed by hyperinsulinemic-euglycemic clamp, is continuously associated with a greater risk of increasing albuminuria [18].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Serum DPP4 activity is also higher in T2DM individuals with IR compared to those without [16]. DPP4 is highly expressed on kidney cell surface and data are available to suggest that DPP4 levels may associated with of renal function [17]. Moreover, insulin sensitivity, assessed by hyperinsulinemic-euglycemic clamp, is continuously associated with a greater risk of increasing albuminuria [18].…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, we also demonstrated that systolic and diastolic blood pressure are lowest in the first tertile and that systolic blood pressure correlates positively with enzymatic activity. With respect to this and the recent data on high expression of this enzyme in the kidney [17] there is a possibility that kidney function may play a role in DPP4 serum activity. Following the data interpretation in the light of indexes of kidney function, DPP4 serum activity remained independently associated with lower insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, urinary excretion of MV-associated DPP-IV is increased in T2DM patients, and the levels of MV-associated DPP-IV in urine are positively correlated with the urinary albumin/ creatinine ratio [127] . Therefore, MV-associated DPP-IV in urine may be an early marker of renal damage before the onset of albuminuria [127] .…”
Section: Mvs In Diabetic Microvascular Complicationsmentioning
confidence: 95%
“…Elevated levels of endothelial-derived MVs and monocytederived MVs may serve as biomarkers for nephropathy progression in T2DM [14,55,74] . A recent study showed that MVassociated dipeptidyl peptidase-IV (DPP-IV) is the major form of DPP-IV in urine, which is secreted from tubular epithelial cells and is related to early tubular impairment [127] . Moreover, urinary excretion of MV-associated DPP-IV is increased in T2DM patients, and the levels of MV-associated DPP-IV in urine are positively correlated with the urinary albumin/ creatinine ratio [127] .…”
Section: Mvs In Diabetic Microvascular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation